2003
DOI: 10.1038/sj.bjc.6600908
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for bladder cancer using E1B-55 kD-deleted adenovirus in combination with adenoviral vector encoding plasminogen kringles 1–5

Abstract: Mutations or loss of heterozygosity of p53 are detected in approximately 50% of bladder cancers. E1B-55 kD-deleted adenovirus has been shown to kill tumour cells with defective p53 function while sparing normal cells. Here, we examined the cytolytic effect and replication of E1B-55 kD-deleted adenovirus, designated Ad5WS1, on human bladder cancer cell lines with various p53 status. Ad5WS1 caused more severe cytolytic effect and replicated more efficiently in J82 and TCC-SUP bladder cancer cells carrying mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Approximately 90% of human bladder tumors are present as transitional cell tumors [4,5]. It has been reported that transitional cell tumors are among the most highly prevalent cancers diagnosed in adults, and are a common cause of death through genitourinary tumors [6,7]. Hence, it is believed that transitional cell carcinoma in the elderly population is becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of human bladder tumors are present as transitional cell tumors [4,5]. It has been reported that transitional cell tumors are among the most highly prevalent cancers diagnosed in adults, and are a common cause of death through genitourinary tumors [6,7]. Hence, it is believed that transitional cell carcinoma in the elderly population is becoming increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…Ad5WS1 (E1B-55 kDadeleted, selectively replicating adenovirus) and Ad.LacZ (E1A-deleted, replication-defective adenovirus encoding h-galactosidase) have been described previously (18,19). To insert a multiple cloning site at nucleotide 525 of adenovirus genome, which is immediate upstream of the E1A open reading frame, the adenovirus region from bases 343 to 1,003 was generated by PCR using pAd5WS1 as the template.…”
Section: Methodsmentioning
confidence: 99%
“…Based on IC 50 values, HT-1376 cells were f170 times more sensitive to 5-FU than MBT-2 cells, which may have decreased their sensitivity threshold to Ad-hTERT-CD/5-FC. Among different bladder cancer cells used in this study, TSGH-8301 cells, which exhibited the lowest hTERT promoter activity but intermediate 5-FU sensitivity, were the most susceptible bladder cancer cell line to adenoviral infection (39). Nevertheless, TSGH-8301 cells were the least sensitive cell line to Ad-hTERT-CD/5-FC-induced cytotoxicity (Fig.…”
Section: Discussionmentioning
confidence: 98%